Circulating Galectin-3 and Aldosterone for Predicting Atrial Fibrillation Recurrence after Radiofrequency Catheter Ablation - Zhong-bao Ruan; Run-feng Gao; Fei Wang; Ge-cai Chen; Jun-guo Zhu; Yin Ren; Li Zhu (Cardiovascular Therapeutics)
Background. Circulating galectin-3 (Gal-3) and aldosterone (ALD) are involved in fibrosis and inflammation. However, their potential value as predictors of atrial fibrillation (AF) recurrence after radiofrequency catheter ablation (RFCA) is unknown or controversial. Therefore, the aim of this study was to assess the relationship between baseline Gal-3, ALD levels, and AF recurrence in patients performing RFCA. Methods. 153 consecutive patients undergoing RFCA were included. Gal-3 and ALD were measured at baseline. Univariate and multivariate Cox regressions were performed to determine the predictors of AF recurrence. Receiver operating characteristic (ROC) curve and Kaplan-Meier (K-M) curve were used to assess the value of predictors. Results. There were 35 (22.88%) cases of AF recurrence after RFCA. The recurrence group had significantly higher preoperative serum levels of Gal-3 and ALD than the nonrecurrence group. Univariate and multivariate analysis showed that Gal-3 (HR=1.28, 95% CI: 1.04-1.56, p=0.02) and ALD (OR=1.02, 95% CI: 1.00-1.03, p<0.03) were significantly associated with AF recurrence after RFCA. The area under the curve (AUC) of preoperative serum Gal-3, ALD, and 2 combined to predict the recurrence of AF patients after RFCA was 0.636, 0.798, and 0.893, respectively, while sensitivity was 65.32%, 71.69%, and 88.61%, respectively and specificity was 77.46%, 78.53%, and 86.0%, respectively. Patients with Gal-3 above the cutoff value of 14.57 pg/ml had higher frequent AF recurrence than the patients with Gal−3≤14.57 pg/ml (35% vs. 12%, p<0.001) during a follow-up. Meanwhile, patients with ALD above the cutoff value of 243.61 pg/ml also had a higher AF recurrence rate than those with ALD≤243.61 pg/ml (37% vs. 11%, p<0.001) during a follow-up. The recurrence rate in patients with Gal−3>14.57 pg/ml+ALD>243.61 pg/ml was higher than that in patients with baseline Gal−3>14.57 pg/ml or ALD>243.61 pg/ml and patients with Gal−3≤14.57 pg/ml+ALD≤243.61 pg/ml (57% vs. 14% vs. 9%, p<0.01, respectively). Conclusion. AF recurrence after RFCA had higher baseline Gal-3 and ALD levels, and higher preoperative circulating Gal-3 and ALD levels were independent predictors of AF recurrence for patients undergoing RFCA, while combination of preoperative Gal-3 and ALD levels has higher prediction accuracy.